War and Myth: The Might of Myth in the Kosovo War in 1999 - Enuka, Chuka (SOSIOHUMANIKA, 2013)
ABSTRACT: This paper concentrates on the connectedness between myth and war. It pictures myth as a causal explanation for war, and mirrors mythâs might and roles in erupting and exacerbating the war in Kosovo in 1999. Myths are often related to situations where people seek to construct, legitimize, and contest their social identities and ownerships. Most societies are held together by myth-system. Within such systems, foundation myths purport to explain the origins and destiny of a nation. Although they may be false in significant ways, foundation myths are usually accepted uncritically by people. They tell dramatic stories about a nationâs sacred history and this serves as the exemplary model for all significant political activities. Though the Kosovo War is traced to problematic factors that are many and mixed, but from all available indications, part of the factors for the war can be understood from the perspective ofÂ  contending and competing mythological recounting by the Kosovo-Serbs and Kosovo-Albanians of their past. Both sidesâ arguments for right over Kosovo are based on a complex interpretation of mythological details. The big question that begs to be addressed is how to reconcile the two diametrically opposing mythical interpretations of historical and legal developments in Kosovo? The finding of this paper is that the failure to achieve a harmonization of the two mythological accounts exacerbated the hotly contested indigeneity question, leading Kosovo and its occupants to a catastrophic war that claimed several thousands of lives. KEY WORD: Between myth and war, war in Kosovo, foundation myths, Kosovo-Serbs and Kosovo-Albanians, and interpretations of historical events.Â RESUME: Makalah ini berjudul âPerang dan Mitos: Kekuatan Mitos dalam Perang Kosovo pada tahun 1999â. Fokus tulisan ini pada keterkaitan antara mitos dan perang. Ianya menggambarkan mitos sebagai suatu penjelasan sebab-akibat untuk perang, dan mencerminkan kekuatan mitos dan perannya dalam menimbulkan dan memperburuk perang di Kosovo pada tahun 1999. Mitos seringkali berhubungan dengan situasi dimana orang-orang berusaha untuk menciptakan, mensyahkan, dan memperjuangkan identitas sosial dan kepemilikan mereka. Kebanyakan masyarakat disatukan oleh sistem-mitos. Dalam sistem tersebut, mitos-mitos dasar diakui untuk menjelaskan asal-usul dan nasib suatu bangsa. Walaupun mitos-mitos tersebut mungkin salah dalam hal-hal penting, namun biasanya diterima secara tidak kritis oleh masyarakat. Mitos-mitos tersebut mengisahkan cerita-cerita dramatis tentang sejarah pengorbanan suatu bangsa dan hal ini bertindak sebagai model contoh bagi semua kegiatan politik yang penting. Walaupun Perang Kosovo berawal dari faktor-faktor problematis yang sangat banyak dan beragam, tetapi dari semua indikasi yang ada, salah satu faktor untuk perang dapat difahami dari perspektif cerita mitos yang bersaing dan menantang oleh orang-orang Kosovo-Serbia dan Kosovo-Albania tentang masa lalu mereka. Argumen kedua belah pihak untuk hak asasi bagi Kosovo berdasarkan suatu interpretasi yang rumit tentang seluk-beluk mitos. Pertanyaan besar yang diajukan adalah bagaimana untuk menyatukan dua interpretasi mitos yang bertentangan secara diametral tentang sejarah dan perkembangan resmi di Kosovo? Temuan dalam makalah ini bahwa kegagalan untuk mencapai keharmonisan dua cerita mitos memperburuk pertanyaan tentang keaslian yang bersaing panas, yang menuntun Kosovo dan penduduknya kepada perang bencana besar yang menelan ribuan nyawa. KATA KUNCI: Antara mitos dan perang, perang di Kosovo, mitos-mitos dasar, Kosovo-Serbia dan Kosovo-Albania, serta interpretasi peristiwa sejarah.Â ===About the Author: Chuka Enuka, Ph.D. is a Senior Lecturer at the Department of History and International Studies NAU (Nnamdi Azikiwe University) in Awka, Nigeria. Corresponding author is: chukaenuka@yahoo.comHow to cite this article? Enuka, Chuka. (2013). âWar and Myth: The Might of Myth in the Kosovo War in 1999â in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.6, No.1 [Mei], pp.27-40. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 20, 2013); Revised (April 24, 2013); and Published (May 20, 2013). Â  Â